Integritas Perilaku Kepemimpinan Publik Walikota Bandung - Raykevin Bagus Julian Maramis; Kristian Widya Wicaksono (Department of Government Studies Universitas Muhammadiyah Makassar, 2017)
Some of the achievements that Bandung City had today, is a positive value for the performance of Bandung City Government. Public leadership behavior of Bandung City Mayor becomes one of a several factors that increasing the performance of Bandung City Government. The purpose of this study is to discover the tendency of public leadership behaviours of Bandung City Mayor based on five dimensions namely: accountability leadership, lawfulness leadership, ethical leadership, political loyal leadership, dan network governance leadership. The method of this research is a quantitative descriptive study, by using data collection techniques such as questionnaires from 30 respondents and interviews. The results of this study shows that the tendency of public leadership behavior of the mayor of Bandung City is inclined to the lawfulness leadership with a good category . This evidence comes from the behavior of the public leadership of Bandung City Mayor which always emphasize every employee to always obey and properly follow the rules and regulations that has been established. Beberapa prestasi yang telah diraih oleh Kota Bandung di masa kepemimpinan Walikota Bandung saat ini, merupakan suatu nilai positif bagi kinerja Pemerintah Kota Bandung. Perilaku kepemimpinan publik dari Walikota Bandung menjadi salah satu faktor peningkatan kinerja dari Pemerintah Kota Bandung. Tujuan dari penelitian ini adalah ingin mengetahui kecenderungan perilaku kepemimpinan publik dari Walikota Bandung dilihat dari lima dimensi yaitu: accountability leadership, lawfulness leadership, ethical leadership, political loyal leadership, dan network governance leadership. Pada penelitian ini, peneliti menggunakan jenis penelitian kuantitatif deskriptif, menggunakan teknik pengumpulan data berupa kuesioner dan wawancara. Hasil dari penelitian ini menunjukan bahwa kecenderungan perilaku kepemimpinan publik dari Walikota Bandung adalah cenderung pada lawfulness leadership dengan kategori yang baik. Hal ini terlihat dari perilaku kepemimpinan publik dari Walikota Bandung yang selalu menekankan setiap pegawainya untuk selalu menaati dan secara benar mengikuti aturan dan regulasi yang telah ditetapkan.